مفهوم السَّداد في القرآن الكريم - Belaouda, Djamilla; Faris , Waleed Fekry (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma’rifah), 2020)
This study examines the concept of sadād (setting right) in the Qur’an, an important concept that plays a role in both building the thought and the character of the individual. The concept of sadād, moreover, plays an important role in guiding the notion of istikhlāf (the notion of humans being God’s vicegerent on earth) towards ʿibādiyyah (servitude) and framing it within righteous speech and virtuous actions. The study links the concept of sadād with the concept of ṣalāḥ (righteousness or virtue), the latter being an outcome or product of the former. The study also investigates the broader concept of sadād (beyond the individual) which manifests in many places of the Qur’an. This broader concept may be referred to as “cosmic sadād” or “universal sadād.” The study thus aims to understand the concept of sadād and its universal characteristics according to the Qur’an. The study also attempts to clarify the difference between the concept of sadād and the concept of ṣawāb, two Qur’anic concepts that are similar but actually carry distinct meanings. Sadād typically refers to the context of human endeavour (i.e., setting it right), while ṣawāb refers to righteous behavior. Lastly, the study investigates the role these concepts play in forming istikhlāf.